Sosialisasi Keamanan Digital dan Pencegahan Kejahatan Siber di SMAN 1 Air Joman : Pengabdian - Muhammad Yasin; Seprina Aulia Putri; Adhistya Aulia DH; Syahrul; Ferry Cahyadi; Ilham Habinsaran; Fikri Vahriza (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
KKN (Real Work Lecture) is a community service program in which students apply their academic knowledge in real-world contexts. One of the initiatives carried out was a digital security awareness program at SMAN 1 Air Joman, designed to improve students’ understanding, pratical skills, and awareness in dealing with cybercrime threats. This study used a descriptive method with pre-test and post-test questionnaires distributed to 40 eleventh-grade students. The results showed significant improvements in three areas. In knowledge, students’ understanding of personal data protection, types of cybercrime, and the ability to identify hoaxes increased from an average of 35-30% to 85-90%. In practice, the use of strong passwords, two-step verification, and caution toward suspicious links rase from 28-42% to 78-92%. In awareness, students intending to apply digital safety in daily life grew from 37% to 93%, and 95% found the program highly beneficial. These findings indicate that KKN-based socialization effectively prevents cybercrime and is worth continuing as a sustainable school program highly beneficial. These findings indicate that KKN-based socialization effenctively prevents cybercrime and is worth continuing as a sustainable school program